Strength properties of nanoporous materials: A 3-layered based non-linear homogenization approach with interface effects. (June 2017) - Brach, Stella; Dormieux, Luc; Kondo, Djimedo; Vairo, Giuseppe
Abstract: In this paper, the strength properties of a ductile nanoporous material are investigated by means of a non-linear homogenization approach based on the modified secant method. The material is described as a rigid-ideal-plastic solid matrix, obeying to a von Mises strength criterion, and containing isotropically-distributed spherical nanovoids. Aiming to properly account for local strain-rate heterogeneities, a 3-layered model is adopted. A novel closed-form macroscopic strength criterion is established, and successfully compared with available numerical data. Proposed approach results in an effective enhancement of the non-linear homogenization-based model recently provided by Dormieux and Kondo (2013).